Dinamika Kehidupan Beragama pada PTKIN di Aceh: Perspektif Kultural dan Historis - Ismail, Sanusi (Perkumpulan Program Studi Sejarah Se-Indonesia, 2023)
This article discusses the dynamics of religious life that occur on the campuses of State Islamic Religious Universities (PTKIN) in Aceh. PTKIN in Aceh is part of PTKIN nationally, and to a certain extent, the religious dynamics between campuses interact and influence each other, on the other hand, its location in Aceh, has a sociocultural impact and the history of Aceh, which has its own Islamic color. Does the dynamics of religious life at PTKIN in Aceh reflect the dynamics of religious life in Acehnese society, or does it have a different style and be more national in nature as part of PTKIN? The main focus of this study is to see whether the dynamics of religious life at PTKIN in Aceh are based on a contextual and tolerant understanding of religion and whether there are indications of the development of radicalism and violence in the name of religion as has occurred in the last decade in various places in Indonesia, including Aceh. The method used is qualitative, where data collection is carried out using in-depth interviews, focus group discussions, observation, and documentation, while data analysis uses critical discourse analysis. In general, it can be concluded that the dynamics of religious life at PTKIN in Aceh are currently more moderate and tolerant compared to the religious dynamics of Acehnese society in general.